Penerapan Teori Behavoir menurut J.B Watson dalam Mengatasi Perilaku Mencontek pada Siswa - Harahap, Akhir Pardamean; Azmi, Say; Baskoro, Dwi Syahfitri; Munthe, Sarmila Yanti (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2023)
One form of dishonesty that often occurs among students is cheating behavior. Cheating behavior occurs at almost every level of education, especially at the school level. Cheating is an inappropriate action for every student to take in school, but it is undeniable that teachers will always find students who cheat in class. Even so, the teacher must be able to change the cheating behavior of these students. One of the theoretical approaches that can be used by a teacher in dealing with cases of cheating in the classroom is the behavioristic theory pioneered by JB Watson. This study aims to describe the application of JB Watson's learning theory in overcoming cheating behavior in students. The background of the authors raised this research because there are so many students who like to cheat so that cheating behavior has become a habit among students.